AGILE GOVERNANCE: TRANSFORMASI TATA KELOLA PARIWISATA TELUK TOMINI GORONTALO, INDONESIA - Aneta, Yanti; Yunus, Resmiyati; Pakaya, Rahmatia; Hulinggi, Pebriyanto A. (Universitas Bina Taruna Gorontalo, 2025)
This study aims to examine the Transformation of Tomini Bay Tourism Governance through the application of Agile Governance as a strategy to improve human resources in the tourism sector of Tomini Bay, Gorontalo. Agile Governance is a governance approach that is responsive and adaptive to change, enabling public organizations to face dynamic challenges. Institutional revitalization in this context aims to increase the effectiveness of coordination, synergy between stakeholders, and strengthen the role of human resources in managing leading tourist destinations in Tomini Bay. This study uses a descriptive qualitative method with a case study approach. The data collection technique was carried out through in-depth interviews and analysis of related policy documents. The results of the study show that the implementation of Agile Governance can increase flexibility in governance, strengthen cross-sector synergy, and improve the quality of human resources in tourism management. The main challenges faced include sectoral egos, limited funding, and lack of competence of local human resources. This study concludes that Agile Governance can be an effective solution in increasing regional tourism competitiveness if supported by inclusive and collaborative policies.